INVESTIGATION OF THE INHIBITION EFFECT OF IONIC LIQUIDS ON METHANE HYDRATES - DADEBAYEV, DIDAR (IRC, 2017)
iv ABSTRACT In oil and gas industry, flow assurance term refers to provision of safe and economic delivery of hydrocarbon stream from the source point to process facilities. Blockages in transmission pipelines, leading to failed flow assurance, can arise serious problems, from both safety and economic perspectives. Formation of natural gas hydrates is the main source of concern for oil and gas industry. At the moderate conditions of high pressure and low temperature, high amount of natural gas molecules are trapped in the cage molecules of frozen water, creating gas hydrates inside pipeline. Safety issues and massive production loss are inevitable if accumulation of gas hydrates occurs in subsea pipelines. Nowadays, there are several techniques to mitigate gas hydrates formation. Chemical inhibition is considered as the most feasible and suitable method among them. In this project, the performance of four ionic liquids (ILs) as thermodynamic hydrate inhibitors was studied. A high pressure micro differential scanning calorimeter was used to detect the dissociation temperature for methane gas hydrates at different pressure points ranging from 5.1 and 11.1 MPa. All aqueous ionic liquid solutions were prepared with the mass fraction of 10 wt%. Eventually, the performance of tested ionic liquids was compared with commercial inhibitors, such as monoethylene glycol and methanol. Moreover, enthalpy values of methane hydrate dissociation were identified by Clausius-Clapeyron relation using the onset dissociation temperature data. Results obtained indicate that all ionic liquids shift the methane hydrate equilibrium line to the direction of a lower temperature and higher pressure. It was found that 1-methylimidazolium hydrogen sulfate, [MIM-HSO4], is the best thermodynamic inhibitor among all the ionic liquids tested. It showed better results than [MEG]. The obtained enthalpy values of methane hydrate dissociation in the presence of ionic liquids were found, ranging from 51.55 to 65.99 kJ/mol.